A Analysis of Regional Competitiveness in the Context of Socio-Economics and Infrastructure - Tampubolon, Dahlan (Future Science / FSH-PH Publications, 2022)
The research aims to analyze the variables that influence and determine the regional competitiveness of Meranti Islands Regency using Analytical Hierarchy Process (AHP) method. The research used primary data with questionnaire and interview with 40 respondents consisting of members of the Regency DPRD, sub-district heads, heads of government sections, socio-cultural and village community empowerment. The research consists of five institutional variables; socio-political, regional labor, economy, productivity and physical infrastructure. The results of regional competitiveness among sub-districts are economic variables in the Tasik Putri Puyu sub-district (0.475), Tebing Tinggi subdistrict’s physical infrastructure (0.373), labor and productivity of Pulau Merbau sub-district (0.216), Rangsang Pesisir Barat sub-district’s high cliff institutions (0.260) and Rangsang Pesisir sub-district’s social politics (0.333).